ANALISIS TENAGA KERJA DAN INVESTASI TERHADAP NILAI PRODUKSI INDUSTRI ALAS KAKI DI KABUPATEN MOJOKERTO - ABIDIN, MOHAMMAD ZAINAL; WIWOHO, BAMBANG (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
ABSTRACTÂ This study aims to (1) find out how big the influence of labor and investment partially to the production and (2) to know how big the influence of labor and investment simultaneously to production. This research was conducted in Mojokerto regency using secondary data of time series from 2013 until 2017 then analyzed by using multiple regression. The results showed that (1) Investment has a significant effect on the production of 0.015, while the labor variable has no significant effect on the production of 0.830. (2) Investment and labor affects simultaneously to production with a significance level of 0.000.Â Keywords: Labor, Investment, Production.